Numerical construction of deformation field in a converging channel - Syafikah, Ayob; Nor Alisa, Mohd Damanhuri; Intan Sabariah, Sabri (2021)
The algorithm of a numerical method for constructing the deformation of the granular material’s flow. This algorithm developed to construct the stress,